The role of proprotein convertase subtilisin-kexin type 9 (PCSK9) in the vascular aging process - is there a link? - Malwina Grobelna; Ewa Strauss; Zbigniew Krasiński (Termedia Publishing House, 2019)
Lately there are many new, promising low-density lipoprotein cholesterol reducing therapies with PCSK9 inhibitors. We performed selected sampling of the publications in PubMed and made a review according to selected keywords. It summarizes the effect of PCSK9 on vascular aging, directly associated with lipid and glucose metabolism, chronic inflammation, atherosclerosis and hypertension. Serum level of PCSK9 is different in patients affected by certain illnesses (whose risk increases with age) than in healthy individuals. The same could be observed in the case of chronic inflammation. In this review we summarize what is known about the role PCSK9 in human metabolism and how this could affect the vascular aging process. Based on the available sources, we prove that PCSK9 is involved in many biochemical pathways associated with vascular aging. In the future, treatments using PCSK9 inhibition may not only reduce the cardiovascular risk but also slow down this process.